Prostaglandin-associated periorbitopathy syndrome (PAPS): Addressing an unmet clinical need. (19th May 2022) - Sakata, Rei; Chang, Pei-Yao; Sung, Kyung Rim; Kim, Tae-Woo; Wang, Tsing-Hong; Perera, Shamira A; Cantor, Louis B
ABSTRACT: Background: Topical prostaglandin analogs (PGAs) are widely approved and preferred first-line options for glaucoma and elevated intraocular pressure (IOP). However, prostaglandin-associated periorbitopathy syndrome (PAPS) is now a well-recognized clinical and cosmetic concern for patients receiving PGAs, especially during long-term and unilateral therapy. PGA-associated periocular changes occur in a substantial proportion of patients, with older patients (>60 years) at greater risk of clinical presentation. PAPS may hinder long-term management of glaucoma, including treatment adherence, ophthalmic surgery outcomes, and reliable IOP measurements. Recommendation: New therapeutic approaches may address this unmet clinical need. Omidenepag isopropyl (OMDI) is a novel, non-prostaglandin, selective EP2 receptor agonist in ongoing development, which provides a unique pharmacological mechanism of action. OMDI appears to provide IOP reductions comparable to PGAs, but without PAPS-related undesirable effects. OMDI may offer a suitable long-term option for patients who demonstrate decreased efficacy, or failure, of PGAs, plus patients with significant PAPS, while fulfilling international guidelines.